Il sacrificio nei testi gnostici - Filoramo, Giovanni 1945- (2001)
The article reviews those Gnostic texts in which the subject of sacrifice arises, examining in the first part the texts that are not Valentinian and in the second part those which are Valentinian. The subject of sacrifice, in fact, occupies a by no means secondary role in the genesis itself of the Pleroma. The hypothesis examined here is that the events surrounding Sophia may be reinterpreted as an application to the last eon of the sacrificial scheme of Lev 16.
Keywords: Opfer